Readiness, acceptance and use of e-health systems in hospitals and health centers of north western ethiopia - Abinew Ali Ayele (Institute of Advanced Engineering and Science, 2020)
The purpose of this empirical study was to examine e-health readiness, acceptance and use in hospitals and health centers in Ethiopia. In this study, 900 samples were taken using a simple random sampling method from 10 Hospitals and 20 health centers in northwestern Ethiopia. SmartPls software was used for the structural equation modeling and path analysis techniques. All of the e-health readiness indicators, except employees’ attitudes showed that hospitals and health centers were not ready to implement and use e-health systems. The intentions of users to accept and use e-health systems were evaluated and determinants were identified. Service quality from the technological factors, self-efficacy from the human factors and user training from the organizational factors were found to be significant determinants of user satisfaction, individual performance, and organizational performance respectively. Major determinants were an organizational performance with a contribution of 37.6% influence followed by an individual performance with 28.2% contribution (together accounted for about 65.8% influence) of the users’ behavioral intentions to use e-health systems. The model, which explained 47.6 % of the variances in the data, was found to be significant.